Ayurvedic Management of Hidradenitis Suppurativa (International Journal of Ayurveda and Pharma Research, 2025)
Hidradenitis Suppurativa (HS) could be agonizing skin condition that causes skin abscesses and scarring on the skin. It is one of the most distressing dermatological conditions which affects the person’s life quality. Exact cause is unknown, but it occurs in areas rich in apocrine glands such as axilla, groin, peri anal, perineal and infra mammary area etc. This condition is having high psychosocial impact. In Ayurveda it can be considered under Nadi vrana. There are many Chikitsa principles are explained. Management of hidradenitis along with Agadatantra principles needs special attention. Methods: Here we report a case of hidradenitis suppurativa having painful mucopurulent abscesses over both axilla and buttocks. Sodhana and Visha chikitsa principles were used for management of this condition. Results: Purulent discharge and foul smelling completely relieved and thickness of lesion got reduced. Conclusion: Management of skin lesions having chronic onset can be managed with principles of Ayurveda and Visha chikitsa.